Joint Task Force for Clinical Trial Competency and Clinical Research Professional Workforce Development - Sonstein, Stephen A.; Jones, Carolynn T. (Frontiers in Pharmacology, 2018)
Clinical research workforce development efforts have focused on both increasing the size of the workforce of investigators and professionals working in the clinical research enterprise, but also the education and training of those individuals to ensure the quality of study performance to improve the public’s health. A major contribution to these efforts has been the establishment of core competencies for clinical research professionals by the Joint Task Force for Clinical Trial Competency. This article reviews the development of the clinical research core competencies, their wide adoption and influence on job descriptions, education, training and academic accreditation.